No scalpel vasectomy, a novel technique for permanent male sterilization – Our institutional experience - Ramakrishnan, Rajkumar; Ponnusamy, Periasamy; Poovathai, Senthilkumar; Sangreshi, Vinayak; Shravankumar Savadatti; Gopu Rakesh Vamsi (Asian Journal of Medical Sciences, 2023)
Background: No scalpel vasectomy (NSV) is a novel modern innovation technique wherein vas deferens is delivered, ligated, and excised without use of a scalpel. It is a permanent sterilization option for male with low complication rate and greater patient compliance and low morbidity. Aims and Objectives: The objective of this study was to analyze the effectiveness, safety, complications, and acceptability of NSV. Materials and Methods: A total of 140 vasectomies were performed using NSV technique in Government Mohan Kumaramangalam Medical College and Hospital, Salem, Tamil Nadu, India. during December 2020–November 2022 (24 months). Results: A study of operative time, effectiveness, and complications of the procedure were analyzed. The mean age of patients was 34 with 2 Nos of children on an average. The average operative time was 10 min with a range of 8–30 min. No cases required for conversion into standard incisional vasectomy. Complication of NSV included bleeding – in 3 cases (2%), hematoma – in 2 cases (1.4%), wound infections – in 3 cases (2%), and scrotal pain – in 4 cases (2.8%) which were managed conservatively. There was no failure of NSV reported during follow-up of these cases. Conclusion: NSV is an effective, safe, cost-effective, and permanent male contraceptive procedure, with very minimal manageable complications. India is fighting population explosion and does need this technique to be popularized among the people.